2020
DOI: 10.3390/foods9091188
|View full text |Cite
|
Sign up to set email alerts
|

The Flavor of Dairy Products from Grass-Fed Cows

Abstract: The milks used for manufacturing bovine dairy products are not all equal. The feeding regimen of lactating cows can widely vary, giving rise to remarkable compositional differences. Recently, grass-fed/based milk and transformed products are being taken into great consideration due to their more favorable nutritional characteristics and better sustainability over those from intensive systems. Besides these well-established aspects, the existence of differences in flavor is highly debated. The “cheese story tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…The potential source and aroma of each of these VOC have already been discussed. As mentioned, 3-/4-ethylphenol is a phenolic compound that has been previously identified in bovine milk (2,6,41) and appears to be present in both raw GRS and TMR milk in this study. 3-/4-ethylphenol was identified in both feed samples being higher in TMR feed, which concurred with the results found by Faulkner et al (6).…”
Section: Aroma Active Volatiles In Raw Tmr Milk By Aedasupporting
confidence: 68%
See 3 more Smart Citations
“…The potential source and aroma of each of these VOC have already been discussed. As mentioned, 3-/4-ethylphenol is a phenolic compound that has been previously identified in bovine milk (2,6,41) and appears to be present in both raw GRS and TMR milk in this study. 3-/4-ethylphenol was identified in both feed samples being higher in TMR feed, which concurred with the results found by Faulkner et al (6).…”
Section: Aroma Active Volatiles In Raw Tmr Milk By Aedasupporting
confidence: 68%
“…Dimethyl sulfone is derived from the oxidation of dimethyl sulphide, which may be formed via the metabolism of methionine and/or cysteine ( 27 ), or from heat-induced oxidation of methionine ( 34 ). It may also be transferred directly from plant-based diets ( 2 ), but this was not evident in this study ( Supplementary Table 1 ). Similar to the branched acids and aldehydes, numerous studies have found higher abundances of dimethyl sulfone in bovine milk derived from a pasture-feeding system than from a concentrate-feeding system ( 2 , 4 , 28 , 35 ), suggesting it is likely related to the increased availability of more digestible protein (methionine) in the pasture-based feeding system, which, again, contradicts the findings of this study.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…) destacou que o leite de vacas alimentadas com pastagem é cada vez mais apreciado pelo consumidor. As razões para essa valorização envolvem a sustentabilidade ambiental, bem-estar animal, valores éticos (vantagens cientificamente comprovadas) e melhor composição do leite, mais saudável e possivelmente com características sensoriais diferenciadas (ainda sendo investigadas)(CABIDDU et al, 2019;FACCIA, 2020).Cabiddu et al. (2019) destacam que o leite de vacas a pasto é mais rico nutricionalmente, possuindo mais vitaminas, polifenóis, enzimas e até mesmo ácidos graxos, contribuindo com a saúde humana.…”
unclassified